N-type material for thermoelectric conversion, method for producing same, thermoelectric conversion element, and dopant

By doping the dopant into the p-type material for thermoelectric conversion, n-type material for thermoelectric conversion has been successfully realized, which solves the problem of difficulty in conversion in the prior art and improves the thermoelectric conversion performance of the material.

CN119817200APending Publication Date: 2025-04-11DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063396.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-09-01
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to convert p-type materials for thermoelectric conversion to n-type materials for thermoelectric conversion, resulting in limited material applications in the field of thermoelectric conversion.

Method used

By doping a dopant selected from the group consisting of sulfinates and disulfites into a p-type material for thermoelectric conversion containing carbon nanotubes and conductive resins, the impregnation and solvent removal steps are performed to realize n-type transformation of the p-type material for thermoelectric conversion.

Benefits of technology

The p-type material for thermoelectric conversion is successfully converted into n-type material for thermoelectric conversion, which improves the Seebeck coefficient and conductivity of the material, and is suitable for the application of thermoelectric conversion components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005294265740000061
    Figure BDA0005294265740000061
  • Figure BDA0005294265740000071
    Figure BDA0005294265740000071
  • Figure BDA0005294265740000191
    Figure BDA0005294265740000191
Patent Text Reader

Abstract

Disclosed is a method for producing an n-type material for thermoelectric conversion, which comprises a step for doping a dopant into a p-type material for thermoelectric conversion that contains carbon nanotubes and a conductive resin, and wherein the dopant contains at least one compound selected from the group consisting of sulfinates and dithionates. The method includes: an impregnation step in which at least one portion of the p-type material for thermoelectric conversion is impregnated with a dopant solution containing a dopant and a solvent; and a solvent removal step for removing the solvent. The concentration of the dopant in the dopant solution is 15 mM or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an n-type material for thermoelectric conversion and a method for producing the same, a thermoelectric conversion element and a dopant. Background Art

[0002] Thermoelectric conversion is a technology that directly converts heat into electricity using the Seebeck effect, and has attracted attention as an energy recovery technology that converts waste heat generated when using fossil fuels into electricity.

[0003] Thermoelectric conversion elements used in such fields are preferably bipolar elements having both a material exhibiting p-type conductivity and a material exhibiting n-type conductivity, but most nanomaterials exhibit p-type conductivity. Therefore, a technology for converting a nanomaterial exhibiting p-type conductivity into a nanomaterial exhibiting n-type conductivity is required.

[0004] For example, Patent Document 1 discloses an n-type dopant that converts a nanomaterial exhibiting p-type conductivity into a nanomaterial exhibiting n-type conductivity.

[0005] It should be noted that whether the nanomaterial exhibits p-type conductivity or n-type conductivity can be determined by the positive or negative value of the Seebeck coefficient. When the Seebeck coefficient is positive, the nanomaterial exhibits p-type conductivity, and when the Seebeck coefficient is negative, the nanomaterial exhibits n-type conductivity.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2015 / 198980 Summary of the invention

[0009] Problems to be solved by the invention

[0010] A main object of the present invention is to provide a method for producing an n-type material for thermoelectric conversion that can convert a p-type material for thermoelectric conversion into an n-type material for thermoelectric conversion.

[0011] Means for solving problems

[0012] The inventors of the present application have conducted intensive studies to solve the above-mentioned problems and, as a result, have found that a predetermined p-type material for thermoelectric conversion can be converted to an n-type material by doping a predetermined dopant, thereby completing the present invention.

[0013] That is, the present invention provides the method for producing an n-type material for thermoelectric conversion described in [1] and [2], the n-type material for thermoelectric conversion described in [3] and [4], the thermoelectric conversion element described in [5], and the dopant described in [6] and [7].

[0014] [1] A method for producing an n-type material for thermoelectric conversion, comprising a step of doping a dopant into a p-type material for thermoelectric conversion containing carbon nanotubes and a conductive resin, wherein the dopant comprises at least one compound selected from the group consisting of sulfinates and dithionites, the step comprising: an impregnation step of impregnating at least a portion of the p-type material for thermoelectric conversion with a dopant solution containing the dopant and a solvent; and a solvent removal step of removing the solvent, wherein the concentration of the dopant in the dopant solution is 15 mM or more.

[0015] [2] The production method according to [1], wherein the dopant comprises at least one compound selected from the group consisting of sodium methanesulfinate, sodium hydroxymethanesulfinate, and sodium dithionite.

[0016] [3] An n-type material for thermoelectric conversion, which is obtained by doping a p-type material for thermoelectric conversion containing carbon nanotubes and a conductive resin with a dopant, wherein the dopant comprises at least one compound selected from the group consisting of sulfinates and dithionites.

[0017] [4] The n-type material for thermoelectric conversion according to [3], wherein the dopant includes at least one compound selected from the group consisting of sodium methanesulfinate, sodium hydroxymethanesulfinate, and sodium dithionite.

[0018] [5] A thermoelectric conversion element comprising the n-type material for thermoelectric conversion according to [3] or [4].

[0019] [6] A dopant that is doped into a p-type material for thermoelectric conversion containing carbon nanotubes and a conductive resin to convert the p-type material for thermoelectric conversion into an n-type material, wherein the dopant comprises at least one compound selected from the group consisting of sulfinates and dithionites.

[0020] [7] The dopant according to [6], wherein the dopant comprises at least one compound selected from the group consisting of sodium methanesulfinate, sodium hydroxymethanesulfinate, and sodium dithionite.

[0021] Effects of the Invention

[0022] According to the present invention, a method for manufacturing an n-type material for thermoelectric conversion capable of converting a p-type material for thermoelectric conversion into an n-type material for thermoelectric conversion is provided. In addition, an n-type material for thermoelectric conversion obtained by such a manufacturing method is provided. In addition, according to the present invention, a thermoelectric conversion element using such an n-type material for thermoelectric conversion is provided. In addition, according to the present invention, a novel dopant capable of forming such an n-type material for thermoelectric conversion is provided. DETAILED DESCRIPTION

[0023] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.

[0024] In this specification, the numerical range represented by "~" represents a range including the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively. In the numerical ranges recorded in stages in this specification, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical ranges recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the values ​​shown in the embodiments.

[0025] In this specification, unless otherwise specified, the materials exemplified below may be used alone or in combination of two or more within the scope of the conditions. In the case where there are multiple substances belonging to each component, unless otherwise specified, the content of each component refers to the total amount of the multiple substances.

[0026] In this specification, whether the thermoelectric conversion material shows p-type conductivity or n-type conductivity can be judged by the positive or negative of the Seebeck coefficient. When the Seebeck coefficient is positive, the thermoelectric conversion material shows p-type conductivity, and the material having such a property is called a p-type material for thermoelectric conversion. When the Seebeck coefficient is negative, the thermoelectric conversion material shows n-type conductivity, and the material having such a property is called an n-type material for thermoelectric conversion. The Seebeck coefficient can be measured, for example, using the measurement method in the embodiments described later, and the polarity of the thermoelectric conversion material can be judged based on the positive or negative value of the measured value.

[0027] <n-type materials for thermoelectric conversion>

[0028] The n-type material for thermoelectric conversion according to one embodiment is obtained by doping a dopant into a p-type material for thermoelectric conversion. The portion of the p-type material for thermoelectric conversion doped with the dopant becomes the n-type material for thermoelectric conversion.

[0029] (p-type material for thermoelectric conversion)

[0030] The p-type material for thermoelectric conversion contains carbon nanotubes and a conductive resin.

[0031] The carbon nanotubes may be single-layer, double-layer, or multi-layer (three or more layers), but are preferably single-layer from the viewpoint of further improving the Seebeck coefficient and electrical conductivity of the thermoelectric conversion material (p-type material for thermoelectric conversion and n-type material for thermoelectric conversion described later).

[0032] The carbon nanotubes preferably include single-walled carbon nanotubes. The content of the single-walled carbon nanotubes relative to the total amount of the carbon nanotubes is preferably 25% by mass or more, more preferably 50% by mass or more, and may be, for example, 100% by mass.

[0033] The diameter of the single-walled carbon nanotube is not particularly limited, and may be, for example, 20 nm or less, preferably 10 nm or less, and more preferably 3 nm or less. It should be noted that the lower limit of the diameter of the single-walled carbon nanotube may be, for example, 0.4 nm or more, or 0.5 nm or more.

[0034] In this specification, the diameter of a single-walled carbon nanotube can be determined by Raman spectroscopy, based on the wavelength between 100 and 300 cm -1 The wave number of the peak appearing in (ω(cm -1 )) is calculated using the formula: diameter (nm) = 248 / ω.

[0035] As an evaluation method for single-walled carbon nanotubes, the G / D ratio in laser Raman spectroscopy is known. In the present embodiment, the G / D ratio of the single-walled carbon nanotube in the laser Raman spectrum at a wavelength of 532 nm is preferably 10 or more, more preferably 20 or more. By using such single-walled carbon nanotubes, there is a tendency to obtain a p-type material for thermoelectric conversion with better electrical conductivity. It should be noted that the upper limit of the above-mentioned G / D ratio is not particularly limited, for example, it can be 500 or less, or 300 or less.

[0036] The content of carbon nanotubes may be, for example, 20% by mass or more, preferably 30% by mass or more, and more preferably 40% by mass or more, based on the total amount of solid components of the p-type material for thermoelectric conversion. The content of carbon nanotubes may be, for example, 99% by mass or less, preferably 95% by mass or less, and more preferably 90% by mass or less, based on the total amount of solid components of the p-type material for thermoelectric conversion.

[0037] The conductive resin is not particularly limited, and known conductive resins used in p-type materials for thermoelectric conversion can be used. As the conductive resin, for example, resins including polyaniline conductive polymers, polythiophene conductive polymers, polypyrrole conductive polymers, polyacetylene conductive polymers, polyphenylene conductive polymers, polyparaphenylene vinyl conductive polymers, etc. can be cited. As the polythiophene conductive polymer, poly(3,4-ethylenedioxythiophene) can be exemplified.

[0038] The conductive resin may be a conductive resin composed of poly(3,4-ethylenedioxythiophene) (hereinafter sometimes referred to as "PEDOT") and an electron acceptor. When such a conductive resin is used, the conductivity of the p-type material for thermoelectric conversion tends to be further improved.

[0039] Examples of the electron acceptor include polystyrene sulfonic acid, polyvinyl sulfonic acid, poly(meth)acrylic acid, polyvinyl sulfonic acid, toluene sulfonic acid, dodecylbenzene sulfonic acid, camphor sulfonic acid, bis(2-ethylhexyl)sulfosuccinate, chlorine, bromine, iodine, phosphorus pentafluoride, arsenic pentafluoride, boron trifluoride, hydrogen chloride, sulfuric acid, nitric acid, tetrafluoroboric acid, perchloric acid, iron (III) chloride, tetracyanoquinodimethane, etc. From the viewpoint of further improving the conductivity of the p-type material for thermoelectric conversion, the electron acceptor may be polystyrene sulfonic acid (hereinafter sometimes referred to as "PSS").

[0040] The content of the conductive resin may be, for example, 1% by mass or more, preferably 5% by mass or more, and more preferably 10% by mass or more, based on the total amount of solid components of the p-type material for thermoelectric conversion. The content of the conductive resin may be, for example, 80% by mass or less, preferably 70% by mass or less, and more preferably 60% by mass or less, based on the total amount of solid components of the p-type material for thermoelectric conversion.

[0041] (Dopant)

[0042] In this specification, a dopant refers to a substance that changes the Seebeck coefficient of a material to be doped with the dopant.

[0043] In this specification, “changing the Seebeck coefficient” means decreasing the value of the Seebeck coefficient or changing the value of the Seebeck coefficient from a positive value to a negative value.

[0044] The dopant includes at least one compound selected from the group consisting of sulfinates and dithionites. By doping the p-type material for thermoelectric conversion with such a dopant, the Seebeck coefficient of the p-type material for thermoelectric conversion can be changed, thereby obtaining an n-type material for thermoelectric conversion showing n-type conductivity.

[0045] The reason for the above effect is not necessarily clear, but it is believed that the reason is that the Fermi level of the p-type material for thermoelectric conversion changes due to either a decrease in the carrier concentration of holes or an increase in the carrier concentration of electrons in the p-type material for thermoelectric conversion, or both.

[0046] The sulfinate is a salt formed by a monovalent or divalent cation and a sulfinate anion. Examples of the sulfinate include compounds represented by the following formula (1) and compounds represented by the following formula (2).

[0047] [Chemical formula 1]

[0048]

[0049] In formula (1), R 1 represents a monovalent organic group, M + It represents a monovalent cation.

[0050] R 1 The monovalent organic group represented by may be, for example, an alkyl group, a fluoroalkyl group, a hydroxyalkyl group, an aryl group, a monovalent heterocyclic group, or an aralkyl group.

[0051] The number of carbon atoms of the alkyl group may be, for example, 1 to 20, 1 to 10, 1 to 6, or 1 to 3. The alkyl group may be any of a linear alkyl group, a branched alkyl group, or a cyclic alkyl group. Examples of the linear alkyl group include methyl, ethyl, n-propyl, n-butyl, and n-hexyl. Examples of the branched alkyl group include isopropyl, isobutyl, sec-butyl, and tert-butyl. Examples of the cyclic alkyl group include cyclopentyl and cyclohexyl. The alkyl group may be, for example, a methyl group.

[0052] Fluoroalkyl refers to an alkyl group in which at least a portion of the hydrogen atoms of the alkyl group exemplified above are substituted by fluorine atoms. Specific examples of fluoroalkyl include fluoromethyl, difluoromethyl, trifluoromethyl, 2-fluoroethyl, 1,2-difluoroethyl, 2,2-difluoroethyl, and perfluoroethyl. For example, the fluoroalkyl group may be trifluoromethyl.

[0053] The hydroxyalkyl group refers to an alkyl group in which at least a part of the hydrogen atoms of the alkyl group exemplified above are substituted with a hydroxyl group. Specific examples of the hydroxyalkyl group include a hydroxymethyl group and a hydroxyethyl group. For example, the hydroxyalkyl group may be a hydroxymethyl group.

[0054] Aryl refers to a group formed by removing one hydrogen atom directly bonded to a carbon atom constituting a ring from an aromatic hydrocarbon. Aromatic hydrocarbons include compounds formed by direct bonding of two or more of the group consisting of benzene, hydrocarbon condensed ring compounds containing benzene, and hydrocarbon condensed ring compounds containing benzene. Specific examples of aryl include phenyl, 1-naphthyl, 2-naphthyl, 1-anthryl, 2-anthryl, and 9-anthryl. Some of the hydrogen atoms of the aryl may be substituted by an alkyl group, a fluorine atom, or the like.

[0055] A monovalent heterocyclic group refers to a group formed by removing one hydrogen atom directly bonded to a carbon atom constituting a ring from a heterocyclic compound such as furan, thiophene, pyrrole, tetrahydrofuran, tetrahydrothiophene, pyrrolidine, etc. Specific examples of the monovalent heterocyclic group include furanyl, thienyl, pyrrolyl, tetrahydrofuranyl, tetrahydrothienyl, pyrrolidinyl, etc. Some of the hydrogen atoms in the monovalent heterocyclic group may be substituted by an alkyl group, a fluorine atom, etc.

[0056] Aralkyl refers to an alkyl group in which at least a part of the hydrogen atoms of the alkyl group exemplified above is replaced by the aryl group exemplified above. Examples of the aralkyl group include benzyl, (2-methylphenyl)methyl, (3-methylphenyl)methyl, (4-methylphenyl)methyl, (2,4-dimethylphenyl)methyl, (ethylphenyl)methyl, and naphthylmethyl.

[0057] Examples of the monovalent cation include alkali metal ions such as lithium ions, sodium ions, and potassium ions. The monovalent cation may be, for example, a sodium ion.

[0058] Specific examples of the compound represented by formula (1) include sodium methanesulfinate, sodium hydroxymethanesulfinate (rongalite), sodium trifluoromethanesulfonate, sodium 1,1-difluoroethanesulfinate, sodium cyclohexanesulfinate, sodium tetrahydrofuransulfinate, and the like.

[0059] [Chemical formula 2]

[0060]

[0061] In formula (2), R 2 and R 3 Each independently represents a monovalent organic group, M 2+ It represents a divalent cation.

[0062] R 2 and R 3 The monovalent organic group represented by may be, for example, an alkyl group, a fluoroalkyl group, a hydroxyalkyl group, an aryl group, a monovalent heterocyclic group, or an aralkyl group.

[0063] As R 2 and R 3 The alkyl group, fluoroalkyl group, hydroxyalkyl group, aryl group, monovalent heterocyclic group, or aralkyl group represented by R 1 The alkyl group, fluoroalkyl group, hydroxyalkyl group, aryl group, monovalent heterocyclic group, or aralkyl group represented by R may be, for example, a methyl group. The hydroxyalkyl group may be, for example, a hydroxymethyl group. The fluoroalkyl group may be, for example, a trifluoromethyl group. 2 and R 3 They may be the same as or different from each other, but are preferably the same.

[0064] Examples of the divalent cations include alkaline earth metal ions such as calcium ion and magnesium ion; and ions of Group 12 elements such as zinc ion.

[0065] Specific examples of the compound represented by formula (2) include calcium bis(hydroxymethanesulfinate), zinc bis(hydroxymethanesulfinate) (Safolin), zinc bis(trifluoromethanesulfinate), zinc bis(difluoromethanesulfinate), zinc bis(benzenesulfinate), and the like.

[0066] The dithionite is a salt formed by a monovalent or divalent cation and a dithionite anion. Examples of the monovalent cation include alkali metal ions. Examples of the divalent cation include alkaline earth metal ions, ions of Group 12 elements, and the like.

[0067] Specific examples of the dithionite include sodium dithionite and zinc dithionite.

[0068] From the viewpoint of easily obtaining an n-type material for thermoelectric conversion, the dopant may include at least one compound selected from the group consisting of sodium methanesulfinate, sodium hydroxymethanesulfinate, and sodium dithionite, and may include sodium hydroxymethanesulfinate.

[0069] The dopant may contain components other than at least one compound selected from the group consisting of the above-mentioned sulfinates and dithionites as required. Such components are not particularly limited as long as they do not impair the function of the dopant, and examples thereof include solvents such as water and organic solvents.

[0070] The method for producing an n-type material for thermoelectric conversion obtained by doping a p-type material for thermoelectric conversion with a predetermined dopant is not particularly limited, and the n-type material can be produced, for example, by the following method.

[0071] <Method for producing n-type material for thermoelectric conversion>

[0072] The production method of one embodiment includes a step of doping a p-type material for thermoelectric conversion containing carbon nanotubes and a conductive resin with a dopant (hereinafter sometimes referred to as a "doping step"). The doping step includes an impregnation step and a solvent removal step.

[0073] (Impregnation process)

[0074] This step is a step of impregnating at least a portion of the p-type material for thermoelectric conversion with a dopant solution containing a dopant and a solvent (first solvent).

[0075] The dopant solution can be obtained by mixing the dopant and the first solvent. As the first solvent, for example, water, acetonitrile, acetone, methanol, ethanol, 1-propanol, 2-propanol, ethylene glycol, dimethyl sulfoxide (DMSO), N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, etc. can be cited. The first solvent can include water, for example.

[0076] The concentration of the dopant in the dopant solution is 15 mM or more. When the concentration of the dopant in the dopant solution is 15 mM or more, there is a tendency that the n-type conversion of the p-type material for thermoelectric conversion is fully carried out. From the viewpoint of improving conductivity, the concentration of the dopant in the dopant solution can be 18 mM or more, 20 mM or more, 25 mM or more, 30 mM or more, 35 mM or more, 40 mM or more, 45 mM or more, or 50 mM or more. There is no particular limit to the upper limit of the concentration of the dopant in the dopant solution, for example, it can be 1000 mM or less, 500 mM or less, 200 mM or less, 150 mM or less, or 100 mM or less.

[0077] The dopant solution may contain other components in addition to the dopant and the first solvent within a range that does not impair the effects of the present invention. Examples of other components include a binder resin, an antioxidant, a thickener, and a surfactant.

[0078] There is no particular limitation on the method of impregnating the thermoelectric conversion material with the dopant solution, and examples thereof include a method of adding the dopant solution to the thermoelectric conversion material, a method of immersing the thermoelectric conversion material in the dopant solution, and the like. In the case where a dopant solution containing a dopant and a first solvent is impregnated into a portion of the p-type material for thermoelectric conversion, it is preferred to use a method of adding the dopant solution to the thermoelectric conversion material. On the other hand, in the case where a dopant solution containing a dopant and a first solvent is impregnated into the entire p-type material for thermoelectric conversion, it is preferred to use a method of immersing the thermoelectric conversion material in the dopant solution.

[0079] In one embodiment, the method of impregnating a thermoelectric conversion material with a dopant solution may include the following steps: applying a mixed solution containing carbon nanotubes, a conductive resin, and a solvent (a second solvent) on a support, removing the second solvent from the applied mixed solution, and forming a coating film containing a p-type material for thermoelectric conversion; and impregnating the obtained coating film with a dopant solution. The above method may further include the following steps: after forming the coating film, exposing the obtained coating film to a solvent (a third solvent), and impregnating at least a portion of the third solvent into the coating film.

[0080] The mixed solution can be obtained by mixing carbon nanotubes, a conductive resin, a dispersant, and a second solvent. As the dispersant, for example, a resin, a surfactant, etc. can be cited. The second solvent can be exemplified by the same substance as the first solvent of the dopant solution. The second solvent can include water, for example. The mixed solution can contain other components besides the carbon nanotubes, the conductive resin, the dispersant, and the second solvent.

[0081] As the support, for example, there can be mentioned resin substrates such as polyimide, polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polycarbonate, polyetheretherketone, polyphenylene sulfide, polysulfone, etc.; inorganic substrates such as glass, copper, silver, gold, aluminum, etc. Among them, the support can be a resin substrate selected from the group consisting of polyimide, polyethylene terephthalate and polyethylene naphthalate from the aspect that the obtained thermoelectric conversion material shows good flexibility.

[0082] The method for applying the mixed liquid is not particularly limited, and for example, a doctor blade method, a casting method, a dip coating method, a spray coating method, a spin coating method, etc. can be appropriately selected.

[0083] The method for removing the second solvent from the applied mixed liquid is not particularly limited, and may be appropriately selected from known methods such as heating and reducing pressure according to the type of the second solvent, and a plurality of methods may be combined.

[0084] In this manner, a coating film containing a p-type material for thermoelectric conversion can be obtained. A portion of the second solvent may remain in the coating film.

[0085] When the coating film is exposed to the third solvent, the third solvent may be the same as the first solvent of the dopant solution. The third solvent may include dimethyl sulfoxide (DMSO). By including dimethyl sulfoxide (DMSO) in the third solvent, a small amount of insulating components mixed in the thermoelectric conversion material can be easily removed, and there is a tendency to further improve the mobility of the thermoelectric conversion material.

[0086] The method for exposing the coating film to the third solvent is not particularly limited, and examples thereof include immersing the coating film in the third solvent, applying the third solvent to the coating film, etc. Among them, the method for exposing the obtained coating film to the third solvent may be a method of immersing the coating film in the third solvent, from the aspect of being able to easily expose the coating film to the third solvent while maintaining the shape of the coating film.

[0087] In the process of exposing the coating film to the third solvent, a coating film impregnated with the third solvent is obtained, and the coating film is provided to the next process. It should be noted that, in the third solvent used in the process of exposing the coating film to the third solvent, except for the solvent impregnated or attached to the coating film, it can be removed at the end of this process. For example, in the case where the coating film is immersed in the third solvent in this process, the coating film can be taken out from the third solvent and provided to the next process.

[0088] Next, the obtained coating film is impregnated with the dopant solution. Examples of the method for impregnating the obtained coating film with the dopant solution include a method of adding the dopant solution to the obtained coating film and a method of immersing the obtained coating film in the dopant solution.

[0089] As a method for adding the dopant solution to the obtained coating film, for example, a method of dripping the dopant solution using a pipette can be cited. The dripping amount of the dopant solution is not particularly limited, and can be, for example, 0.01 to 0.5 mL / cm 2 The dopant solution may be added dropwise at room temperature or while being heated. The heating temperature is not particularly limited, and may be, for example, 40°C or higher, 50°C or higher, or 60°C or lower, or 250°C or lower, 225°C or lower, or 200°C or lower.

[0090] In the method of immersing the obtained coating film in the dopant solution, the time for immersing the coating film in the dopant solution may be, for example, 30 seconds to 72 hours, or 1 minute to 24 hours.

[0091] In the impregnation step, a material (coating) impregnated with a dopant solution is obtained, and the material (coating) is subjected to a solvent removal step. It should be noted that, among the first solvents used in the impregnation step, other than the solvent impregnated or attached to the material, the first solvents can be removed at the end of the impregnation step. For example, in the case where the material is immersed in a dopant solution in the impregnation step, the material can be taken out from the dopant solution and subjected to a solvent removal step.

[0092] (Solvent Removal Process)

[0093] This step is a step of removing the first solvent from the p-type material for thermoelectric conversion impregnated with the dopant solution. In this step, the first solvent need not necessarily be completely removed, and the first solvent may remain within a range sufficient to function as the n-type material for thermoelectric conversion.

[0094] The solvent removal step may be, for example, a step of removing the first solvent by natural drying, or a step of removing the first solvent by heating treatment, reduced pressure treatment, or the like.

[0095] The solvent removal step may include a step of heating the thermoelectric conversion material impregnated with the first solvent. In the step of heating the thermoelectric conversion material, it is believed that the first solvent, which increases the compatibility with the conductive resin due to heating, causes the conductive resin in the material to flow, thereby filling the gaps between the carbon nanotubes to form a denser structure. Therefore, by including such a step in the solvent removal step, it is expected that the thermoelectric conversion characteristics of the n-type material for thermoelectric conversion will be more significantly improved.

[0096] The temperature of the heat treatment is not particularly limited, and for example, it may be above 40°C, preferably above 50°C, and more preferably above 60°C. By increasing the temperature of the heat treatment, there is a tendency for the Seebeck coefficient of the thermoelectric conversion material to increase. In addition, the temperature of the heat treatment may be, for example, below 250°C, preferably below 225°C, and more preferably below 200°C. By lowering the temperature of the heat treatment, there is a tendency for the electrical conductivity of the thermoelectric conversion material to increase. With regard to thermoelectric conversion materials, there is a tendency for the Seebeck coefficient and electrical conductivity to change depending on the temperature of the heat treatment. Therefore, the temperature of the heat treatment may be appropriately selected, for example, within the above-mentioned range according to the balance of the numerical values ​​of the Seebeck coefficient and electrical conductivity.

[0097] The time of the heat treatment is not particularly limited, and may be, for example, 1 minute or longer, preferably 10 minutes or longer, or 12 hours or shorter, preferably 6 hours or shorter.

[0098] The heat treatment does not necessarily have to be performed for the purpose of removing the first solvent, and the solvent removal step may be performed after the heat treatment.

[0099] In the above manner, a thermoelectric conversion film including an n-type material for thermoelectric conversion can be obtained.

[0100] The portion of the p-type material for thermoelectric conversion doped with the dopant becomes the n-type material for thermoelectric conversion. When converting the p-type material for thermoelectric conversion into the n-type material for thermoelectric conversion, the entire p-type material for thermoelectric conversion may be doped with the dopant to produce the n-type material for thermoelectric conversion, or a portion of the p-type material for thermoelectric conversion may be doped with the dopant to produce a composite of the p-type material for thermoelectric conversion and the n-type material for thermoelectric conversion.

[0101] In one embodiment of the method for manufacturing an n-type material for thermoelectric conversion, the impregnation step may be a step of impregnating a dopant solution containing a dopant and a first solvent into a portion of a resin layer containing a p-type material for thermoelectric conversion, and the solvent removal step may be a step of removing the first solvent from the resin layer impregnated with the dopant solution to obtain a thermoelectric conversion film containing a p-type material for thermoelectric conversion and an n-type material for thermoelectric conversion. According to such an embodiment, a thermoelectric conversion film containing a p-type material and an n-type material can be easily obtained. In addition, in such an embodiment, by appropriately setting the range of the impregnation dopant solution in the impregnation step, a thermoelectric conversion film having a desired p / n structure can be easily obtained.

[0102] The shape of the n-type material for thermoelectric conversion is not particularly limited. For example, as described above, a coating film of the p-type material for thermoelectric conversion formed on a support may be doped with a predetermined dopant to obtain a thermoelectric conversion film containing the n-type material for thermoelectric conversion in the form of a film supported on a support.

[0103] From the viewpoint of obtaining appropriate resistance and excellent flexibility, the film thickness of the coating film containing the p-type material for thermoelectric conversion and the thermoelectric conversion film containing the n-type material for thermoelectric conversion is preferably 100 nm to 1 mm, more preferably 200 nm to 800 μm, and further preferably 300 nm to 600 μm.

[0104] The n-type material for thermoelectric conversion of the present embodiment can be suitably used as an n-type material for a thermoelectric conversion element. In addition, the n-type material for thermoelectric conversion of the present embodiment can also be suitably used for applications such as a Peltier element and a temperature sensor.

[0105] <Thermoelectric conversion element>

[0106] A thermoelectric conversion element according to one embodiment includes the above-mentioned n-type material for thermoelectric conversion.

[0107] The thermoelectric conversion element of this embodiment may include, for example, two conductive substrates and a thermoelectric conversion film disposed between the conductive substrates and containing the above-mentioned n-type material for thermoelectric conversion. In addition, the thermoelectric conversion layer may further contain a p-type material for thermoelectric conversion.

[0108] As the conductive substrate, various known conductive substrates can be used. From the perspective of being less prone to corrosion and dissolution, the conductive substrate may include at least one conductive material selected from the group consisting of tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), and stainless steel.

[0109] The two conductive substrates may also be referred to as a first electrode and a second electrode, respectively.

[0110] The thermoelectric conversion element of the present embodiment can be produced, for example, by a method including a lamination step of arranging a thermoelectric conversion film including an n-type material for thermoelectric conversion and a p-type material for thermoelectric conversion on a conductive substrate.

[0111] The thermoelectric conversion element of the present embodiment can be manufactured, for example, by a method comprising the following steps, namely: a first stacking step, in which a resin layer containing a p-type material for thermoelectric conversion is arranged on a conductive substrate; an impregnation step, in which a dopant solution containing a dopant and a first solvent is impregnated into a portion of the resin layer; a solvent removal step, in which the first solvent is removed to obtain a thermoelectric conversion film containing an n-type material for thermoelectric conversion and a p-type material for thermoelectric conversion; and a second stacking step, in which another conductive substrate is stacked on the thermoelectric conversion film.

[0112] The thermoelectric conversion element may also have a structure other than the above. For example, the thermoelectric conversion element may also have: a sealing material for sealing the thermoelectric conversion film; wiring for electrically connecting the thermoelectric conversion elements to each other or for extracting power to an external circuit; a heat insulating material or a heat conductive material for controlling the thermal conductivity of the thermoelectric conversion element, etc.

[0113] As mentioned above, although the preferred embodiment of the present invention was described, the present invention is not limited to the above-mentioned embodiment.

[0114] Example

[0115] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples. Unless otherwise specified, the following operations were carried out at room temperature (23° C.).

[0116] (Example 1)

[0117] <Preparation of mixed solution>

[0118] A mixed solution was prepared in such a manner that the content of carbon nanotubes and the content of PEDOT / PSS were 1 (50 mass%):1 (50 mass%) based on the total amount of the first coating film (solid content of p-type material for thermoelectric conversion). Specifically, 50 g of a carbon nanotube dispersion (concentration: 0.2 mass%, aqueous dispersion, single-walled carbon nanotubes (diameter: 0.9 to 1.7 nm, G / D ratio: 42.1)) was concentrated by vacuuming until the carbon nanotube concentration became 0.4 mass%. Next, 8.3 g of a PEDOT / PSS aqueous dispersion ("Clevious (registered trademark) PH1000" manufactured by Heraeus Corporation, solid content concentration: 1.2 mass%) and the concentrated carbon nanotube dispersion were fully stirred (stirring time: 30 minutes) using a Threeone Motor ("PM203" manufactured by AS ONE Co., Ltd.). Next, the mixture was fully degassed using a rotation-revolution mixer ("Awatori Rentaro ARE-310" manufactured by Thinky Co., Ltd.) (treatment time: 3 minutes) to prepare a mixed liquid.

[0119] <Formation of the First Coating Film>

[0120] 5 g of the mixed solution was placed on a polyimide film (thickness 25 μm) washed with acetone, coated using a doctor blade with a gap of 2.7 mm, and placed in an air-blowing dryer set at 60° C. and dried for 2 hours. Thus, a first coating film was formed on the polyimide film.

[0121] <Immersion treatment of first coating film>

[0122] The first coating film obtained above on the polyimide film is cut into a size of 1.0 cm × 1.0 cm. The cut first coating film is immersed in 3 mL of dimethyl sulfoxide (DMSO) at room temperature for 120 minutes. Then, it is configured on a heating plate set at 60 ° C for 120 minutes to obtain a second coating film exposed to DMSO. The film thickness is measured using a high-precision digital micrometer (Mitutoyo Co., Ltd., MDH-25MB). The film thickness of the portion where the second coating film is formed and the film thickness of the portion where only the polyimide film is formed are measured, and the difference between the two is calculated as the film thickness of the second coating film. The film thickness of the second coating film is 20.3 μm.

[0123] <Preparation of dopant solution>

[0124] A 20 mM (mmol / L) sodium hydroxymethanesulfinate aqueous solution was prepared by dissolving 0.031 g of sodium hydroxymethanesulfinate dihydrate in 10 mL of water.

[0125] <Addition of dopant solution>

[0126] The obtained second coating film was placed on a hot plate heated to 140° C. Next, a pipette was used to transfer the second coating film at 0.11 mL / cm 2 The above-mentioned dopant solution was added dropwise, and then the mixture was left to stand for 20 minutes to remove the solvent, thereby obtaining a thermoelectric conversion film of Example 1.

[0127] <Measurement of Thermoelectric Conversion Characteristics>

[0128] The Seebeck coefficient (S), conductivity (σ), and power factor (PF) of the thermoelectric conversion film of Example 1 were measured by the following method. The Seebeck coefficient of the thermoelectric conversion film was -21.6 μV / K, the conductivity was 832 S / cm, and the power factor was 39 μW / (mK 2 ).

[0129] Seebeck coefficient

[0130] The Seebeck coefficient of the thermoelectric conversion film is measured by the following method.

[0131] The thermoelectric conversion film disposed on the polyimide film was cut into 10 mm × 10 mm pieces to make test pieces. One end of the long side of the test piece was cooled (the initial temperature of the test piece was -5°C = 18°C), and the other end of the long side of the test piece was heated (the initial temperature of the test piece was +5°C = 28°C). The temperature difference and voltage generated at both ends were measured using a nickel-aluminum-nickel-chromium thermocouple, and the Seebeck coefficient was calculated based on the slope of the temperature difference and voltage.

[0132] Conductivity

[0133] The electrical conductivity was measured by a four-probe method (resistivity meter Loresta GP MCP-T610 manufactured by Nittoseiko Analytech Co., Ltd. (formerly Mitsubishi Chemical Analytech Co., Ltd.), probe: QPP was used).

[0134] Power factor

[0135] The power factor (PF) is calculated using the following formula.

[0136] PF=S 2 σ

[0137] (S: Seebeck coefficient (V / K), σ: conductivity (S / m))

[0138] (Example 2)

[0139] The thermoelectric conversion film of Example 2 was obtained in the same manner as in Example 1 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 20 mM to 30 mM. Table 1 shows the film thickness of the second coating film of Example 2 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0140] (Example 3)

[0141] The thermoelectric conversion film of Example 3 was obtained in the same manner as in Example 1 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 20 mM to 50 mM. Table 1 shows the film thickness of the second coating film of Example 3 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0142] (Example 4)

[0143] The thermoelectric conversion film of Example 4 was obtained in the same manner as in Example 1 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 20 mM to 100 mM. Table 1 shows the film thickness of the second coating film of Example 4 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0144] (Comparative Example 1)

[0145] The second coating film of Comparative Example 1 was obtained in the same manner as in Example 1 except that the dopant solution was not added. Table 1 shows the film thickness of the second coating film of Comparative Example 1 and the results of the thermoelectric conversion characteristics of the second coating film.

[0146] (Comparative Example 2)

[0147] The thermoelectric conversion film of Comparative Example 2 was obtained in the same manner as in Example 1 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 20 mM to 1 mM. Table 1 shows the film thickness of the second coating film of Comparative Example 2 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0148] (Comparative Example 3)

[0149] The thermoelectric conversion film of Comparative Example 3 was obtained in the same manner as in Example 1 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 20 mM to 5 mM. Table 1 shows the film thickness of the second coating film of Comparative Example 3 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0150] (Comparative Example 4)

[0151] The thermoelectric conversion film of Comparative Example 4 was obtained in the same manner as in Example 1 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 20 mM to 10 mM. Table 1 shows the film thickness of the second coating film of Comparative Example 4 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0152] (Comparative Example 5)

[0153] The second coating of Comparative Example 5 was obtained in the same manner as in Comparative Example 1 except that the carbon nanotube dispersion was used only instead of the PEDOT / PSS aqueous dispersion to form the second coating. Table 2 shows the film thickness of the second coating of Comparative Example 5 and the results of the thermoelectric conversion characteristics of the second coating.

[0154] (Comparative Example 6)

[0155] The thermoelectric conversion film of Comparative Example 6 was obtained in the same manner as in Comparative Example 4 except that the carbon nanotube dispersion was used only instead of the PEDOT / PSS aqueous dispersion to form the second coating film. Table 2 shows the film thickness of the second coating film of Comparative Example 6 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0156] (Comparative Example 7)

[0157] The thermoelectric conversion film of Comparative Example 7 was obtained in the same manner as in Comparative Example 6 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 10 mM to 50 mM. Table 2 shows the film thickness of the second coating film of Comparative Example 7 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0158] (Comparative Example 8)

[0159] The thermoelectric conversion film of Comparative Example 8 was obtained in the same manner as in Comparative Example 6 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 10 mM to 75 mM. Table 2 shows the film thickness of the second coating film of Comparative Example 8 and the results of the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0160] (Comparative Example 9)

[0161] The thermoelectric conversion film of Comparative Example 9 was obtained in the same manner as in Comparative Example 6 except that the concentration of sodium hydroxymethanesulfinate in the dopant solution was changed from 10 mM to 100 mM. Table 2 shows the film thickness of the second coating film of Comparative Example 9 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0162] (Comparative Example 10)

[0163] The second coating of Comparative Example 10 was obtained in the same manner as in Comparative Example 1 except that the carbon nanotube dispersion was not used and only the PEDOT / PSS aqueous dispersion was used to form the second coating. Table 2 shows the film thickness of the second coating of Comparative Example 10 and the results of the thermoelectric conversion characteristics of the second coating.

[0164] (Comparative Example 11)

[0165] The thermoelectric conversion film of Comparative Example 11 was obtained in the same manner as in Example 4 except that the carbon nanotube dispersion was not used and only the PEDOT / PSS aqueous dispersion was used to form the second coating film. Table 2 shows the film thickness of the second coating film of Comparative Example 11 and the thermoelectric conversion characteristics of the thermoelectric conversion film.

[0166] [Table 1]

[0167]

[0168] [Table 2]

[0169]

[0170] As shown in Table 1, the thermoelectric conversion films of Examples 1 to 4, which used sodium hydroxymethanesulfinate as a dopant and added a dopant solution at a predetermined concentration, showed a negative Seebeck coefficient and exhibited performance as an n-type material for thermoelectric conversion. On the other hand, the second coating film of Comparative Example 1, which was not doped with a dopant, and the thermoelectric conversion films of Comparative Examples 2 to 4, which added a dopant solution at a concentration lower than the predetermined concentration, showed a positive Seebeck coefficient and did not exhibit performance as an n-type material for thermoelectric conversion.

[0171] In addition, as shown in Table 2, the second coating film of Comparative Example 5 containing only carbon nanotubes and the thermoelectric conversion films of Comparative Examples 6 to 9, and the second coating film of Comparative Example 10 containing only PEDOT / PSS and the thermoelectric conversion film of Comparative Example 11, showed a positive Seebeck coefficient even when a dopant solution was added, and did not show performance as an n-type material for thermoelectric conversion.

[0172] From the above, it was confirmed that the method for producing an n-type material for thermoelectric conversion of the present invention can convert a p-type material for thermoelectric conversion into an n-type material for thermoelectric conversion.

Claims

1. A method for producing an n-type material for thermoelectric conversion, comprising the steps of doping a dopant into a p-type material for thermoelectric conversion containing carbon nanotubes and a conductive resin, and The dopant comprises at least one compound selected from the group consisting of sulfinates and dithionites, The process comprises: An impregnation step of impregnating at least a portion of the p-type material for thermoelectric conversion with a dopant solution containing the dopant and a solvent; and a solvent removal step, removing the solvent, The concentration of the dopant in the dopant solution is 15 mM or more.

2. The manufacturing method according to claim 1, wherein: The dopant includes at least one compound selected from the group consisting of sodium methanesulfinate, sodium hydroxymethanesulfinate, and sodium dithionite.

3. An n-type material for thermoelectric conversion, which is obtained by doping a dopant into a p-type material for thermoelectric conversion containing carbon nanotubes and a conductive resin, The dopant includes at least one compound selected from the group consisting of sulfinates and dithionites.

4. The n-type material for thermoelectric conversion according to claim 3, wherein: The dopant includes at least one compound selected from the group consisting of sodium methanesulfinate, sodium hydroxymethanesulfinate, and sodium dithionite. 5 . A thermoelectric conversion element comprising the n-type material for thermoelectric conversion according to claim 3 .

6. A dopant which is doped into a p-type material for thermoelectric conversion containing carbon nanotubes and a conductive resin to convert the p-type material for thermoelectric conversion into an n-type material, The dopant includes at least one compound selected from the group consisting of sulfinates and dithionites.

7. The dopant according to claim 6, wherein The dopant includes at least one compound selected from the group consisting of sodium methanesulfinate, sodium hydroxymethanesulfinate, and sodium dithionite.

Citation Information

Patent Citations

  • Nanomaterial dopant composition composite, dopant composition, and method for manufacturing nanomaterial dopant composition composite

    WO2015198980A1